Comparative outcomes of extracorporeal membrane oxygenation for COVID-19 delivered in experienced European centres during successive SARS-CoV-2 variant outbreaks (ECMO-SURGES): an international, multicentre, retrospective cohort study. Issue 2 (February 2023) - Schmidt, Matthieu; Hajage, David; Landoll, Micha; Pequignot, Benjamin; Langouet, Elise; Amalric, Matthieu; Mekontso-Dessap, Armand; Chiscano-Camon, Luis; Surman, Katy; Finnerty, Dylan; Santa-Teresa, Patricia; Arcadipane, Antonio; et al.
Summary: Background: To inform future research and practice, we aimed to investigate the outcomes of patients who received extracorporeal membrane oxygenation (ECMO) for acute respiratory distress syndrome (ARDS) due to different variants of SARS-CoV-2. Methods: This retrospective study included consecutive adult patients with laboratory-confirmed SARS-CoV-2 infection who received ECMO for ARDS in 21 experienced ECMO centres in eight European countries (Austria, Belgium, England, France, Germany, Italy, Portugal, and Spain) between Jan 1, 2020, and Sept 30, 2021. We collected data on patient characteristics, clinical status, and management before and after the initiation of ECMO. Participants were grouped according to SARS-CoV-2 variant (wild type, alpha, delta, or other) and period of the pandemic (first [Jan 1–June 30] and second [July 1–Dec 31] semesters of 2020, and first [Jan 1–June 30] and second [July 1–Sept 30] semesters of 2021). Descriptive statistics and Kaplan-Meier survival curves were used to analyse evolving characteristics, management, and patient outcomes over the first 2 years of the pandemic, and independent risk factors of mortality were determined using multivariable Cox regression models. The primary outcome was mortality 90 days after the initiation of ECMO, with follow-up to Dec 30, 2021. Findings: ECMO was initiated in 1345 patients. Patient characteristics and management were similar for the groups of patients infected with different variants, except that those with the delta variant had a younger median age and less hypertension and diabetes. 90-day mortality was 42% (569 of 1345 patients died) overall, and 43% (297/686) in patients infected with wild-type SARS-CoV-2, 39% (152/391) in those with the alpha variant, 40% (78/195) in those with the delta variant, and 58% (42/73) in patients infected with other variants (mainly beta and gamma). Mortality was 10% higher (50%) in the second semester of 2020, when the wild-type variant was still prevailing, than in other semesters (40%). Independent predictors of mortality were age, immunocompromised status, a longer time from intensive care unit admission to intubation, need for renal replacement therapy, and higher Sequential Organ Failure Assessment haemodynamic component score, partial pressure of arterial carbon dioxide, and lactate concentration before ECMO. After adjusting for these variables, mortality was significantly higher with the delta variant than with the other variants, the wild-type strain being the reference. Interpretation: Although crude mortality did not differ between variants, adjusted risk of death was highest for patients treated with ECMO infected with the delta variant of SARS-CoV-2. The higher virulence and poorer outcomes associated with the delta strain might relate to higher viral load and increased inflammatory response syndrome in infected patients, reinforcing the need for a higher rate of vaccination in the population and updated selection criteria for ECMO, should a new and highly virulent strain of SARS-CoV-2 emerge in the future. Mortality was noticeably lower than in other large, multicentre series of patients who received ECMO for COVID-19, highlighting the need to concentrate resources at experienced centres. Funding: None.